PENGARUH MUSABAQAH TILAWATIL QUR’AN TERHADAP KUALITAS HAFALAN AL-QUR’AN SANTRI UNWANUL FALAH NWDI PAOK LOMBOK - Rohdiana, Siti; Hidayati, Nurul; Sya’rani, Muh. (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to determine the effect of musabaqah tilawatil qur'an on the quality of al-qur'an memorization among students at Unwanul Falah NWDI Paok Lombok. The approach used in this study is a quantitative approach with a comparative quantitative research design. This study was conducted at the Unwanul Falah NWDI Paok Lombok Islamic boarding school. The sample for this study consisted of 60 students from Unwanul Falah. The sample was selected using purposive sampling. The results of this study indicate that there is an influence of the Musabaqah Tilawatil Qur'an on the quality of Quran memorization among students at Unwanul Falah NWDI Paok Lombok. This can be seen from the results of the hypothesis test, which showed a significance value (p-value) of 0.000 (less than 0.05), thereby accepting the alternative hypothesis and rejecting the null hypothesis. This means that there is a difference between the quality of Quran memorization among Unwanul Falah students who participated in the Quran recitation competition and those who did not. The difference in average scores between students who participated in the Musabaqah Tilawatil Qur'an and those who did not participate is between 0.563 and 8.085 at a 95% confidence interval (Confidence Interval of the Difference), which also indicates that students who participated in the Quran recitation competition have superior Quran memorization quality compared to those who did not participate in the competition.